Radiological Conditions in Al-Basra Province of Iraq with Residues of Depleted Uranium in Food Animals: Review Article - Aqeel Hussein (Basrah Journal of Veterinary Research)
Naturally occurring uranium ore is abundant in nature and contains several isotopes of uranium. All uranium isotopes are radioactive. However, only Uranium-235 (U-235) is used to produce nuclear power and nuclear weapons. Uranium-235, important for nuclear weapons, is concentrated through uranium enrichment. In the 1970s, due to its high density, the USA started using DU to create bullets and mortar shells. The uranium oxide produced from the dust is mostly deposited inside the vehicle. depleted uranium mainly emits alpha particles. Alpha lack sufficient energy to penetrate through the skin. Exposure to DU outside the human body is not believed to be a serious hazard, but ingestion or inhalation of DU is a significant health threat. Exposure to alpha particles can have a detrimental impact on living cells, potentially leading to kidney damage. Dust that escapes from uranium metal does not usually travel far due to its density. Urine samples from soldiers and civilians in DU ammunition areas show low DU exposure. Contaminated soil ingested by cattle and sheep can contaminate the food chain. However, the transfer factor in animals is relatively low, comparable to the one for transfer to plants.